Plans for better business performance of Sony in Japan - and suggestions for management and financial accounting transparency - Dat Nguyen Duy; Lan Nguyen Thi Ngoc; Huy Dinh Tran Ngoc; Yen Ly Lan; Dung Nguyen Tien; Dat Pham Minh (Zielona Góra: Faculty of Economics and Management Press)
Through years Sony in Japan has shown success in bringing to themarket high quality products, and via technical inventions. Today risk management is one of vital issues in Sony to maintain its reputation in global markets. The purpose of this study is to find out impacts of economic factors at macro level on net profit of a big technological giant like Sony.
Keywords: Sony company; business performance; stock prices; lending rate; market interest rate; firma Sony; wyniki biznesowe; zysk netto; cena akcji; kredyt; rynkowa stopa procentowa